Ceramide synthase 4 and de novo production of ceramides with specific N-acyl chain lengths are involved in glucolipotoxicity-induced apoptosis of INS-1 β-cells - Julien Véret; Nicolas Coant; Evgeny Berdyshev; Anastasia Skobeleva; Nicole Therville; Danielle Bailbé; И. А. Горшкова; Viswanathan Natarajan; Bernard Portha; Hervé Le Stunff (2011)
Pancreatic β-cell apoptosis induced by palmitate requires high glucose concentrations. Ceramides have been suggested to be important mediators of glucolipotoxicity-induced β-cell apoptosis. In INS-1 β-cells, 0.4 mM palmitate with 5 mM glucose increased the levels of dihydrosphingosine and dihydroceramides, two lipid intermediates in the de novo biosynthesis of ceramides, without inducing apoptosis. Increasing glucose concentrations to 30 mM amplified palmitate-induced accumulation of dihydrosphingosine and the formation of (dihydro)ceramides. Of note, glucolipotoxicity specifically induced the formation of C(18:0), C(22:0) and C(24:1) (dihydro)ceramide molecular species, which was associated with the up-regulation of CerS4 (ceramide synthase 4) levels. Fumonisin-B1, a ceramide synthase inhibitor, partially blocked apoptosis induced by glucolipotoxicity. In contrast, apoptosis was potentiated in the presence of D,L-threo-1-phenyl-2-palmitoylamino-3-morpholinopropan-1-ol, an inhibitor of glucosylceramide synthase. Moreover, overexpression of CerS4 amplified ceramide production and apoptosis induced by palmitate with 30 mM glucose, whereas down-regulation of CerS4 by siRNA (short interfering RNA) reduced apoptosis. CerS4 also potentiates ceramide accumulation and apoptosis induced by another saturated fatty acid: stearate. Collectively, our results suggest that glucolipotoxicity induces β-cell apoptosis through a dual mechanism involving de novo ceramide biosynthesis and the formation of ceramides with specific N-acyl chain lengths rather than an overall increase in ceramide content.